Gingival recession, attached gingiva, oral hygiene status. - Rayia J Al-Naimi; Faraed D Salman; Faiz A Al-Sultan (University of Mosul, College of Dentistry, 2004)
The aim of this study was to evaluate dental problems of diabetic adult patients in Mosul City center, to find if there is any variation between age and sex groups and to determine the periodontal treatment needs of the patients. A sample of 194 adult diabetic patients (90 males, 104 females) divided into 6 age groups were examined using plaque and gingival indices by Löe and Silness (1967), Ramfjord calculus index (1959) and Community Periodontal Index of Treatment Needs (CPITN) (1997). The results showed that the mean plaque and gingival indices for the total sample were increasing with age with highly statistically significant difference with no sex variation. Concerning Ramf-jord calculus index, calculus became the most prevalent with very high means for 20-29 years old and above for both sexes, CPITN revealed that healthy sextants exhibited a very low mean of 0.8 for the youngest age group, bleeding on probing was highest in this age group with a mean of 3.4, pockets of 4-5 mm appeared at age 20-29 years and it increases with increasing age. The results revealed that the total sample needed oral hygiene instruction (100%), while prophylaxis was needed in 55.56-100%, surgical intervention and complex care were needed for old ages.